Numerical investigation on the impact of particle density and flow velocity on particle transport and deposition in a randomly oriented fracture - Bouragaa, Kheira; Bennacer, Lyacine; Akacem, Mustapha (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Fractured formations recently gained significant interest as a landscape for securing both energy and groundwater demands, However, the dual role of fracture in transporting fluids and contaminants underscores the need for further investigations to mitigate the impact on human health. This study aims to numerically investigate the combined effect of particle density and flow velocity on their transport and deposition in different fracture orientations.Methods: A 2D particle tracing simulation was implemented accounting for drag and gravity forces on a smooth fracture. The derived particle numbers under the studied scenario e.g., fracture orientation, particle density, and flow velocity, were fitted to a 1D advection-dispersion equation with a deposition term. Results: The model elucidated that both particle densities yielded an increase in the normalized concentration in non-horizontal scenarios as the fracture orientation angle increased. The overall increment led to an observed decrease in the deposition coefficients and was associated with an increase in the dispersion coefficients. Hence the effect was more pronounced for denser particles where gravitational settling dominated, particularly in horizontal fractures. Less dense particles (1.05 g/cm³) were more strongly influenced by hydrodynamic forces, exhibiting lower overall deposition and dispersion across all fracture orientations. Additionally, increased flow velocity enhanced mechanical mixing and amplified dispersion and deposition coefficients. Conclusion: The findings demonstrated a clear dependency on the combined effect of fracture orientation, particle density, and flow velocity. These valuable insights into particle transport mechanisms in fractured media have applications in subsurface flow, contaminant migration, and reservoir engineering.
Keywords: fractured media; particle density; inclination angle; flow velocity; dispersion; deposition